Pulmonary actinomycosis – a diagnostic dilemma - Živković, Vladan; Šarac, Sanja; Popović, Svetlana; Zarić, Miloš; Ristić, Saša; Kostovski, Vanja; Pešić, Jasna; Nikolić, Bojan; Rakonjac, Bojan; Vuković, Jelena (Vojnosanitetski pregled, 2026)
Introduction. Pulmonary actinomycosis is a chronic inflammatory infectious disease caused by anaerobic and/or microaerophilic bacteria of the genus Actinomyces spp. It causes non-specific symptoms in the patient and gives an atypical clinical and radiographic presentation. It is extremely rare and is characterized by the formation of abscesses and fistulas in the lungs or local fibrosis. In the differential diagnosis, diseases and pathological conditions from tuberculosis to neoplastic processes in the lungs must be considered. Case report. We present a 39-year-old patient with an infiltrative lesion in the apex of the right lung and non-specific symptoms. In this patient, actinomycosis was pathohistologically proven after surgical intervention. Within a period of just over a month, a multi-detector computed tomography of the chest and bronchoscopy with transbronchial biopsy and bronchial swab were performed twice. Initially, pulmonary actinomycosis was not suspected. After an atypical resection of the tumor mass in the apex of the right lung and histopathologically proven infection, the patient was treated with antibiotic therapy for 6 months. Further examination was carried out to prove a potential primary or secondary immunodeficiency. Conclusion. Patients with non-specific changes in the lung parenchyma should also be suspected of having actinomycosis, and after diagnosis, it is necessary to supplement the examination to confirm or exclude immunodeficiency.